MENTAL HEALTH COMMUNITY TO BRACE FOR A NEWER GAMING ADDICTION - Ishtiaq, Khadeeja (Journal of Pakistan Psychiatric Society, 2024)
Video game addiction is defined as the steady and repetitive use of the Internet to play games frequently. IGD is now included in DSM-5 under conditions for furthur research.The proposed symptoms of internet gaming disorder include Preoccupation , Withdrawal symptoms , possible (sadness, anxiety, irritability),Tolerance, Inability to reduce playing, unsuccessful attempts to quit gaming , Giving up other activities ,Continuing to game despite problems, Deceiving family members or others about the amount of time spent on gaming. It is estimated that 4.7% of the population is affected by this disease on average, based on research conducted over the previous two decades. In a study done in Pakistan the alarming level of IGD was found in youth in Pakistan (58.9%).Most effective is CBT for Internet addiction (CBT-IA).